Адміністративний позов як категорія адміністративного права - Ківалов, Сергій Васильович; Кивалов, Сергей Васильевич; Kivalov, Sergej (Одеса : Юрид. л-ра, 2014)
In the article there are analyzed different approaches to the definition of the essence and term of the “administrative law suit” as the administrative law category. The attention is accented on three approaches in the definition of the essence of that term: 1) should be defined separately in procedural (applied to the court demand about defense of the violated right, freedom or legal interest) and material (material-legal demand of the plaintiff to the respondent) meaning; 2) has entire nature that reflect the organic junction of two sides (material-legal and procedural); 3) is the procedural institute as application to the administrative court about defense of the violated rights, freedoms, legal interest or realization of competence in the sphere of public-legal relations.
Ківалов С. В. Адміністративний позов як категорія адміністративного права / С. В. Ківалов // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 7-18.
Keywords: адміністративний позов; адміністративне судочинство; категорія; правовий інститут; позовна заява; административный иск; административное судопроизводство; категория; правовой институт; исковое заявление; administrative law suit; administrative legal procedure; category; legal institute; writ